PENDAYAGUNAAN STRUKTUR TEKS WACANA KESEJAHTERAAN RAKYAT DALAM TAJUK RENCANA HARIAN KOMPAS - Wulandari, Yosi (Kajian Linguistik dan Sastra, 2012)
Language usage shows that language has important role and power in changing events. Kompas â a national daily newspaperâ has a unique language characteristic, particularly the one used in editorial. Research on critical discourse analysis of empowering text structure in editorial is crucial to be conducted. The purpose of this research is to explain the empowerment of thematic, schematic, syntactic, and stylistic structure of discourse in Kompas editorial. This is qualitative research of which object is editorial of Kompas and the data is the text structure of educational, health and environment, and social discourse. The data is collected by documentation technique and it is analyzed by content analysis. The findings show that (1) the thematic text structures show the subjectivity of the editorial. The elements of the structure supporting the topics show Kompasâs resolution to take care of poor society who need government help; (2) schematic text structures tend to show important point at the end of editorial; (3) syntactic text structures show that Kompas takes into account its various readers; (4) stylistic text structures criticizing the society problems tend to be neutral and acceptable.